Comparative Analysis of Common Fennel Regenerants Pabout the Main Morpho-Biological Features Basedon And - Sh., Meliboeva Sh. (European Journal of Life Safety and Stability (2660-9630), 2022)
Common fennel (Foeniculum vulgare Mill.) belongs to the Celeryfamily (Apiaceae). It is cultivated mainly for the production of essential oil, which is isolated from the seeds and green mass of the plant. In addition to essential oil, fennel fruits contain fatty oil and protein, so they are widely used in the perfume, cosmetics and food industries. Currently, breeding work is continuing aimed at increasing the yield and mass fraction of essential oil in fruits and green raw materials of this crop. In addition to traditional approaches, biotechnological methods are used to obtain the initial breeding material. It was found that all samples had a plant height of 146.7 to 168 cm, a lower umbrella attachment height of 79.7 to 94 cm, and were suitable for mechanized harvesting.